Prescribing Pattern of Antifungal Drugs in a Tertiary Care Teaching Hospital in Western India - Parth B. Patel; Akanksha Prajapati; Sumit Patel; Vipul Chaudhary; Vasu Rathod (Universitas Padjadjaran, Indonesia, 2023)
Fungal infections are prevalent in a tropical country like India. Pharmacotherapy of fungal disease has been revolutionized by the introduction of relatively less toxic oral drugs, com- bination therapy, and new formulations of older agents. However, data regarding antifungal drug usage patterns in India must be more present. Hence, this study was planned to study the prescribing pattern and to compare the cost of antifungal drugs in patients attending a tertiary care teaching hospital. It was a cross-sectional, observational study carried out at GCS Hospital, Ahmedabad, from April 2021 to Sept 2021. Prescriptions of 130 patients were collected and analyzed using Microsoft Excel version 2013. A total of 213 antifungal drugs were prescribed to 130 patients. Most patients, 81 (62.3%) were from the 18-40 age group. Combined antifungal treatment (Oral + Topical) was prescribed in 77(59.2%). The most common class of antifungal drugs was imidazole 107 (50.23%), and clotrimazole was the most familiar drug. The most common indication for antifungal therapy was tinea cruris (45.38%). An average of 3.75 drugs were prescribed per prescription, of which 1.63 were antifungal drugs. Combined treatment of oral and topical antifungal drugs was common in dermatological practice. However, the cost of the treatment can be reduced by prescribing generic drugs.